Cover Image: Polymer Crystallization Research in China. Issue 2 (25th March 2020) - Men, Yongfeng; Li, Liangbin
Abstract : Yongfeng Men and Liangbin Li, the guest editors of this special issue of Polymer Crystallization, asked one of their colleagues in Changchun to prepare the brush Chinese calligraphy for "Spring" and filled it with POM images of polymer crystalline spherulites. Through this cover image, the guest editors aim to express the prosperous current and future trends of polymer crystallization studies in China.